IDENTIFICATION AND STUDY OF LEPTOSPIROSIS FOCUS IN IRKUTSK REGION - N. V. Breneva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Due to examination of animal breeding workers at the Irkutsk Region a case of human leptospirosis was identified. at the cattle farm of Tugutuy settlement. Due to epizootological-epidemiological study a mixed, leptospirosis focus in Ekhirit-Bulagat district was established, the agent circulation among commensal and wild, small mammals was demonstrated. Continuous pathogenic Leptospira DNA detection during the second, half of 2011, as well as the positive tularemia laboratory results require further study of the focus.